Anthropometric characteristics of bones from a medieval cemetery at Ostrów Lednicki and analysis of pathological changes occuring on them - Ćwirko-Godycki , Michał; Swedborg, Iwona (Anthropological Review, 1978)
A random sample of 200 was taken from a population of 1126 skeletons excavated from the medieval cemetery at Ostrów Lednicki situated on Lednica Lake 17922/207 East Longitude and 5231/30” North Latitude. Measurements of the bones with statistical analysis of variation, analysis of nonquantitative data and reconstruction of faces have been carried out to estimate ethnic origins and other characteristics of the bones. The occurence, frequency and localisation of pathological changes in the whole population of 1126 skoletons are presented. Fractures, injuries and degonerative changes were the most frequent findings. Affected skeletons exhibited 1 to 8 different simultancous pathological conditions. The spine and upper cxtremities were most often affected.